Further Debt Relief for Low-Income Countries : Key Issues and Preliminary Considerations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The International Monetary and Finance Committee at its 2004 Annual Meetings called on the international community to provide assistance including 'further debt relief' to low-income countries for achieving the Millennium Development Goals (MDGs). It reaffirmed the Fund's 'important role' in supporting lowincome countries and called on the Fund to consider 'further debt relief and its financing.' More impetus for this request was provided by various recent proposals (summarized in Annex I). At their meeting in London in February, G7 Finance Ministers expressed their willingness to provide as much as 100 percent multilateral debt relief.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet